(untitled) (Research, Society and Development, 2022)
Psychological capital are positive internal resources that drive workers to handle work tasks efficiently. His studies reveal its relevance in maintaining the worker’s quality of life and mental health. However, there are few investigations dedicated to comparing this construct in different contexts and perspectives. For this reason, the present article aims to verify and compare how two culturally and geographically distinct populations use their psychological capital in work activities. To achieve this objective, the invariance of the factor structure of the PCQ-12 psychological capital scale was verified in hospital health professionals in the countries of Brazil and Portugal. The total number of respondents are 434 workers (Brazil n=212; Portugal n=222). The results reveal that the aforementioned scale was both reliable and invariant in its factor structure in both sample contexts. It is noteworthy that the Portuguese had higher scores in the factors Self-efficacy, Optimism and Hope. This may indicate that Portuguese health institutions provide greater organizational support than Brazilian ones. In general, it is possible to conclude that the PCQ-12 scale is an adequate instrument for comparative studies between Brazilian and Portuguese health workers, and that they do not have significant differences regarding the factors self-efficacy, hope, optimism and resilience.